Malformations of the Atlas Vertebra Simulating the Jefferson Fracture - Gehweiler, John A.; Daffner, Richard H.; Roberts, Leroy (American Journal of Neuroradiology, 1983)
Congenital clefts and aplasias of the atlas vertebra, while rare, are often first encountered in the emergency room setting. Thirty-six patients with atlas malformations and 10 with Jefferson fractures were encountered. Sixteen of the patients with congenital malformations showed bilateral atlantoaxial lateral offset, a finding generally considered to be the result of fracture. The diagnosis of these abnormalities is readily made from plain films by noting their characteristic features. Anomalies produce lateral offset of 1–2 mm. Jefferson fractures produce a greater offset (over 3 mm).